Redistribution as an income mobility process: The identification and measurement of redistribution - Juan Rafael Morillas (Luxembourg Income Study (LIS), 2009)
How can we evaluate the redistributive effect of welfare states? Do tax and transfer systems reduce the level of inequality generated in the market? In order to answer these questions, we need to be equipped with adequate measures of redistribution. Current measures employed in the sociology and politics of redistribution are seriously flawed. This paper elaborates the reasons why we cannot rely on those measures. Furthermore, it develops a framework to statistically identify redistribution as a micro-level income mobility process, and develops an index to measure it. Using data from the Luxembourg Income Study, the paper shows that the new measure of redistribution developed in this paper is empirically distinct from the conventional measures that have been used in the literature. The paper concludes by demonstrating the importance of the new measure of redistribution for improving our understanding of the social and political determinants of redistribution. In particular, it shows that the conventional wisdom in the political economy of redistribution does not hold in the light of the new measure developed in this paper.
Keywords: 330; redistribution; inequality; income mobility; political economy; power resources; partisanship; median voter; Einkommensumverteilung; Indexberechnung; Einkommensverteilung; Soziale Mobilität; Medianwähler-Modell; Sozialstaat